Drought Assessment in Aceh and North Sumatra Using Effective Drought Index - Suhadi; Supari; Iskhaq Iskandar; Muhammad Irfan; Hamdi Akhsan (Science and Technology Indonesia, 2023)
Indonesia has two seasons and witnesses three rainfall patterns throughout the year. Although Aceh and North Sumatra experience low rainfall, the underlying causes of this condition are unknown. Unfortunately, studies on drought in these regions are very limited. This study uses the Effective Drought Index (EDI) to assess drought in these regions using daily rainfall data from 1985–2019 (35 years) from the meteorology, climatology, and geophysics agency stations. These stations are Sultan Iskandar Muda, Malikussaleh, Deli Serdang, and FL Tobing. In this study, the Ocean Niño Index (ONI) and the Dipole Mode Index (DMI) were used to identify El Niño years and positive and negative phases of the Indian Ocean Dipole (IOD). These indices were used to analyze drought-related climatic phenomena. The results obtained indicated that some drought events were not associated with a positive Indian Ocean Dipole or El Niño, as is typically the case. These include the extreme drought in 1989/90 and moderate drought in 1999 at Sultan Iskandar Muda, moderate drought at Malikussaleh (March to June 2008), moderate drought at Deli Serdang in 2010, as well as the drought from January to June 2006 at FL Tobing. Analysis of spatial patterns revealed that moderate droughts were more prevalent than severe and extreme droughts. These drought assessment results are essential for the mitigation of natural catastrophes.